Protein localization of aquaporins in the adult female disease vector mosquito, Aedes aegypti - Picinic, Britney; Paluzzi, Jean-Paul V.; Donini, Andrew (Frontiers in Insect Science, 2024)
The female Aedes aegypti mosquito is a vector for several arboviral diseases, due to their blood feeding behaviour and their association with urban communities. While ion transport in Ae. aegypti has been studied, much less is known about mechanisms of water transport. Rapid water and ion excretion occurs in the adult female mosquito post blood meal and involves a set of organs including the midgut, Malpighian tubules (MTs), and hindgut. The MTs are responsible for the formation of primary urine and are considered the most important site for active transport of ions. Within the cells of the MTs, along with various ion transporters, there are aquaporin water channels that aid in the transport of water across the tubule cell membrane. Six aquaporin genes have been molecularly identified in Ae. aegypti (AQP1-6) and found to be responsible for the transport of water and in some cases, small solutes such as glycerol. In this study, we used immunohistochemistry to localize AaAQP1, 2, 4, 5, and 6 in the adult female Ae. aegypti, in non-blood fed and post blood feeding (0.5 and 24hr) conditions. We further examined the main water transporting aquaporin, AaAQP1, using western blotting to determine protein abundance changes in isolated MTs pre-and post-blood feeding.Using fluorescence in situ hybridization, aqp1 mRNA was found exclusively in the principal cells of female MTs. Finally, we used immunogold staining with transmission electron microscopy to determine subcellular localization of AaAQP1 in the Malpighian tubules under non-blood fed conditions. Interestingly, AaAQP1 was found to be predominantly in the principal cells of the MTs, dispersed throughout the brush border; however, there was also evidence of some AaAQP1 localization in the stellate cells of the MTs.